استخلاص و تشخيص اللسليلوز من نخيل التمر و أهم تطبيقاته - كريمة, بن عبد الله; عبير, براهيمي; شهيرة, بالشيخة (University of El-Oued, 2020)
"يتمحور هذا العمل حول استخلاص وتشخيص السليلوز من بقايا نخيل التمر و أهم تطبيقاته، حيث تهدف هذه الدراسة إلى تسليط الضوء على تثمين مخلفات النخيل وذلك بإعادة تدويرها واستعمال مكوناتها كمواد متجددة. وقد أستخدمت هذه المخلفات كمصدر لإنتاج السليلوز، كما اشتمل هذا العمل على جوانب نظرية حول طرق استخلاص السليلوز، و تشخيصه بعدة تقنيات، كالمجهر الإلكتروني الماسح (SEM) والمجهر الالكتروني النافذ(TEM) بغية تحديد الخصائص البنيوية(المورفولوجية) لأليافها، وباستعمال تقنية الأشعة السينية (XRD) من أجل تحديد نسبة السليلوز المتبلورة التي وصلت إلى نسبة 87.5% في الدراسات السابقة، و تقنية التحليل الكيميائي الطيفي (EDS) لمعرفة العناصر الكيميائية، وكذلك مطيافية الأشعة تحت الحمراء(IR) لتحديد المجاميع الوظيفية للسليلوز، و من هذا الأخير يتم استخراج العديد من المركبات (المشتقات)التي تحظى بتطبيقات واسعة في عدة مجالات من بينها : الصناعة الإلكترونية، وصناعة الورق والكرتون وغيرها. " "Thiswork revolves around extracting and characterization cellulose from date palm and its most important applications, as this study aims to shed light on the valuation of palm waste by recycling and using its components as renewable materials.These residues were used as a source for the production of cellulose.This work included theoretical aspects of cellulose extraction methods, followed by extensive characterization of cellulose using several techniques, such as scanning electron microscopy (SEM) and transmission electron microscopy (TEM) in order to determine the structural (morphological) characteristics of its fibers, and by using X-ray technology (XRD) for Determination of the percentage of crystallized cellulose that reached 87% in previous studies, the technique of chemical analysis spectroscopy (EDS) to find out the chemical elements, as well as the use of infrared spectroscopy (IR) to determine the functional groups of the extracted cellulose. From nano-cellulose, many materials (composites) are extracted that have wide applications in several fields, including: electronic industry, paper and cardboard industry, polymer industry and others. "
Génie chimiqueمذكرة ماستر تخصص
Keywords: السليلوز، المواد اللجنوسليلوزية، الألياف النباتية، مخلفات النخيل، الاستخلاص.; "Cellulose, Lignocellulose Materials, Plant Fibers, Palm Waste, Extraction. "